Manejo de semillas de 100 especies forestales de América Latina - Salazar, Rodolfo; Soihet, Carolina; Méndez, José Miguel (Serie técnica.Manual técnico / CATIE ;, 2000)
Pag. Guazuma ulmifolia Lam. 1 Virola koschnyi Warb. 3 Gliricidia sepium (jacq.) Kunth ex Walp. e 5 Vochysia ferruginea Mart. 7 Albizia guachapele (Kundh) Dugand 9 Vochysia guatemalensis Donn. Sm. 11 Cordia alliodora (Ruiz & Pav.) Oken 13 Tabebuia rosea (Bertol.) DC. 15 Samanea saman (Jacq.) Merr. 17 Terminalia amazonia (J.F. Gmel.) 19 Pinus caribaea Morelet 21 Pinus tecunumanii Eguiluz & Perry 23 Pinus pseudostrobus Lindl. 25 Pinus maximinoi H. E. Moore 27 Erythrina poeppigiana (Walp.) D.F. Cook. 29 Hyeronima alchomeoides Allemao 31 Bombacopsis quinata (Jacq.) Dugand 33 Alnus acuminata Kunth 35 Leucaena lecocephala (Lam.) de Wit 37 Cupressus lusitanica Mill. 39 Swietenia macrophylla King 41 Pinus oocarpa N/D 43 Tabebuia chrysantha (Jacq.) G. Nicholson 45 Cedrela odorata L. 47 Enterolobium cyclocarpum (Jacq.) Griseb. 49 Pentaclethra macroloba (Willd.) Kuntze 51 Quercus costaricensis Liebm. 53 Terminalia oblonga (Ruiz & Pav.) Steud. 55 Magnolia poasana (Pittier) Dandy. 57 Astronium graveolens Jacq. 59 Ceiba pentandra (L.) Gaertn. 61 Carapa guianensis Aubl. 63 Dipteryx panamensis (Pittier) Record & Mell 65 Dalbergia retusa Hemsl. 67 Swietenia hurnilis Zucc. 69 Cassia grandis L.F. 71 Inga edulis Mart. 73 Zanthoxylum mayanum Standl. 75 Prosopis juliflora (SW.) DC. 77 lnga Vera Willd. 79 Catalpa longissima (Jacq.) Dum. Cours. 81 Guarea guara (Jacq.) P. Willson 83 Leucaena salvadorensis (HBK.) Muell. Arg. 85 Hevea brasiliensis Mull. Arg. 87 Pinus occidentalis Swartz 89 Ochroma pyramidale (Cav. ex Lam.) Urb. 91 Cedrela tonduzii C. DC. 93 Rhizophora mangle L. 95 Cordia dentata Poir. 97 Colubrina arborescens (Mill.) Sarg. 99 Caesalpina velutina (Briff & Rose) Standl. 101 Anacardium excelsum (Bertero & Balb. ex Kunth) 103 Calycophylium candidissimun (Vahl) DC. 105 Magnolia yoroconte Dandy 107 Abies guatemalensis Rehder 109 Bursera simaruba (L.) Sarg. 111 Minquartia guianensis Aub. 113 Calophyllum brasiliense Cambess 115 Jacaranda copaia (Aubi.) D.Don 117 Platymiscium pinnatum (Jacq.) Dugand 119 Calliandra calothyrsus Meisn. 121 Acacia famesiana (L.) Willd. 123 Pithecellobium dulce (Roxb.) Benth. 125 Schizolobium parahyba (Vell.) S.F. Blake 127 Hymenaea corbaril L. 129 Stryphnodendron microstachyurn Poepp. & Endl. 131 Guaiacum officinale L. 133 Simarouba glauca DC. 135 Lafoensia punicifolia DC. 137 Mastichodendron capiri (A.D.C.) Cronquist var tempisque 139 Mimosa scabrella Benth. 141 Genipa americans L. 143 Salix humboldtiana Willd. 145 Sterculia apetala (Jacq.) H.Karst. 147 Andira inermis (W.Wright) Kunth 149 Araucaria angustifolia (Bertol.) 0. Kuntze 151 Didymopanax morototoni (Aublet) Decaisne et Planchon 153 Cordia trichotoma (Vellozo) Arrabida ex Steudel 155 Jacaranda micrantha chamisso 157 Dalbergia nigra (Vell. Conc.) Benth. 159 Myroxilon balsamun (L.) Harms 161 Juglans neotropica Diels 163 Prosopis tamarugo F. Phil. 165 Jacaranda mimosifolia D. Don 167 Araucaria araucana (Mol.) K. Koch 169 Cedrela fissilis Vell. 171 Liquidambar styraciflua L. 173 Brosimum alicastrum Sw. 175 Nothofagus dornbeyi (Mirbel) Oerst. 177 Myrocarpus frondosus Fr. All. 179 Ulmus mexicana (Liebm.) Planch. 181 Balfourodendron riedelianurn Engil. 183 Taxodium mucronatum Ten. 185 Sapindus saponaria L, 187 Quercus oleoides Schidtl. & Cham. 189 Avicennia germinans (L.) Stearn. 191 Peltogyne purpurea Pittier 193 Podocarpus macrostachyus Parl. 195 Diphysa robiniodes Benth. 197 Laguncularia racemosa (L.) C.F. Gaertn. 199 Indice por familia 201 Indice por especie